Entrust we must: The role of "trust" in Somali economic life - Neil C. M. Carrier; Hannah Elliott (Danish Institute for International Studies (DIIS), 2018)
"Trust" is a concept that has received much attention in studies of informal economies which operate in large part outside of formal state regulation. Somali trade provides a pertinent case. In Somalia, across Somali East Africa and beyond, business has thrived, in spite of - or, some would argue, partially because of - the statelessness of the homeland. Beyond scholarly uses, "trust" is also a concept used by Somalis themselves to explain their entrepreneurial success. This Working Paper asks what the concept of "trust" reveals and conceals about Somali economic life, examining the concept in both its etic and emic uses. It does so drawing on ethnographic fieldwork in Eastleigh, an estate in Nairobi's Eastlands, whose economy is, in many ways, exemplarily "informal", and driven by Somali enterprise and capital investments. We argue that while the concept of "trust" can help explain the social relations underpinning trade, and in particular the provision of credit, trust is not a prerequisite for acts of trusting in business. Rather, acts of trusting can themselves work to produce trust, even though they do not eliminate deceit and mistrust in the estate. Trust in its emic usage emerges as a normative rather than descriptive discourse that creates a moral impetus for acts of trusting, even as "trusters" may not necessarily fully trust those they do business with. In Eastleigh, an important driver of this discourse is the demand for credit, which itself plays a crucial role in driving the estate's economy.
Keywords: 330